Programmed Cell Death Recruits Macrophages Into the Developing Mouse Cochlea - Borse, Vikrant; Kaur, Tejbeer; Hinton, Ashley; Ohlemiller, Kevin; Warchol, Mark E. (Frontiers in Cell and Developmental Biology, 2021)
Programmed cell death (PCD) plays a critical role in the development and maturation of the cochlea. Significant remodeling occurs among cells of the greater epithelial ridge (GER) of Kollikers organ, leading to tissue regression and formation of the inner sulcus. In mice, this event normally occurs between postnatal days 5-15 (P5-15) and is regulated by thyroid hormone (T3). During this developmental time period, the cochlea also contains a large population of macrophages. Macrophages are frequently involved in the phagocytic clearance of dead cells, both during development and after injury, but the role of macrophages in the developing cochlea is unknown. This study examined the link between developmental cell death in the GER and the recruitment of macrophages into this region. Cell death in the basal GER begins at P5 and enhanced numbers of macrophages were observed at P7. This pattern of macrophage recruitment was unchanged in mice that were genetically deficient for CX3CR1, the receptor for fractalkine (a known macrophage chemoattractant). We found that injection of T3 at P0 and P1 caused GER cell death to begin at P3, and this premature PCD was accompanied by earlier recruitment of macrophages. We further found that depletion of macrophages from the developing cochlea (using CX3CR1DTR/+ mice and treatment with the CSF1R antagonist BLZ945) had no effects on the pattern of GER regression. Together, these findings suggest that macrophages are recruited into the GER region after initiation of developmental PCD, but that they are not essential for GER regression during cochlear remodeling.